Interchangeability of meningococcal group C conjugate vaccines with different carrier proteins in the United Kingdom infant immunisation schedule. Issue 5 (29th January 2015) - Ladhani, Shamez N.; Andrews, Nick J.; Waight, Pauline; Hallis, Bassam; Matheson, Mary; England, Anna; Findlow, Helen; Bai, Xilian; Borrow, Ray; Burbidge, Polly; Pearce, Emma; Goldblatt, David; et al.
Highlights Immune responses of infants were assessed 1 month after the national UK schedule. Infants could receive any of three meningococcal C conjugate vaccines at 3 and 4 months. Responses were lower after CRM-conjugated followed by tetanus-conjugated MenC vaccine. Conjugate vaccines with different carrier proteins may not be interchangeable. When possible children should receive conjugate vaccines with the same carrier protein.